Evidence of early defence to Ascochyta lentis within the recently identified Lens orientalis resistance source ILWL180. (25th March 2018) - Dadu, R. H. R.; Ford, R.; Sambasivam, P.; Gupta, D.
Abstract : In plant–pathogen interactions, strong structural and biochemical barriers may induce a cascade of reactions in planta, leading to host resistance. The kinetic speed and amplitudes of these defence mechanisms may discriminate resistance from susceptibility to necrotrophic fungi. The infection processes of two Ascochyta lentis isolates (FT13037 and F13082) on the recently identified ascochyta blight (AB)‐resistant Lens orientalis genotype ILWL180 and two cultivated genotypes, ILL7537 (resistant) and ILL6002 (susceptible), were assessed. Using histopathological methods, significant differences in early behaviour of the isolates and the subsequent differential defence responses of the hosts were revealed. Irrespective of virulence, both isolates had significantly lower germination, shorter germ tubes and delayed appressorium formation on the resistant genotypes (ILWL180 and ILL7537) compared to the susceptible genotype (ILL6002); furthermore, these were more pronounced on genotype ILWL180 than on genotype ILL7537. Subsequently, host perception of pathogen entry led to the faster accumulation and notably higher amounts of reactive oxygen species and phenolic compounds at the penetration sites of the resistance genotypes ILWL180 and ILL7537. In contrast, genotype ILL6002 responded slowly to the A. lentis infection and reaffirmed previous gross disease symptomology reports as highly susceptible. Interestingly, quantification of H2 O2 was markedly higher in ILWL180 particularly at 12 h post‐inoculation compared to ILL7537, potentially indicative of its superior resistance capability. Faster recognition of A. lentis is likely to be a major contribution to the superior resistance observed in genotype ILWL180 to the highly aggressive isolates of A. lentis assessed.